Adaptive behaviors on new normal after the COVID -19 epidemic of elderly in elderly club at Ban Pong District in Ratchaburi Province - Tangwong, Supranee; Changmai, Sakul; Pokho, Sirames (Thai Journal of Nursing, 2022)
The purposes of this research were to examine adaptive behaviors on new normal of elderly after the epidemic situation of COVID-19, and to compare their the adaptive behaviors based on the Roy Adaptation Model among those who had personal data differences.. A sample of 120 elderly was purposively selected. The research instruments consisted of a questionnaire on personal data including community characteristics, income, disease, and perception of COVID-19 information, and 2) the adaptive behaviors on new normal assessment including the physiologic mode, the self-concept mode, the role function mode, and the interdependence mode. Its content validity index was 0.89 and the reliability coefficient was 0.82. Descriptive statistics, and t-test were used in data analysis. The results revealed that the adaptive behaviors on new normal after the epidemic situation of COVID-19 of elderly was at the very good level, and those in the urban area had better adaptive behaviors than those in the rural area.